2018
DOI: 10.1038/s41598-018-29414-6
|View full text |Cite
|
Sign up to set email alerts
|

Habitat suitability for the invasion of Bombus terrestris in East Asian countries: A case study of spatial overlap with local Chinese bumblebees

Abstract: Invasive species such as Bombus terrestris represent a severe threat that can result in the decline of local biodiversity. We examined the habitat suitability for B. terrestris invasion in East Asian countries and the risk of habitat overlap with 24 bumblebee species from different groups in China. All East Asian countries were predicted to be susceptible to invasion by B. terrestris, with the highest habitat suitability occurring in China followed by Japan, North Korea, South Korea and Mongolia. Within China,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 63 publications
3
31
1
Order By: Relevance
“…In other areas in the Middle East, the endemicity of flies increased because of a high suitability. This agreed with the FAO report about the geospatial demarcation of OWSF in the Middle East 51 . This report confirmed the influence of temperature on the potential distribution of OWSF in the Middle East.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In other areas in the Middle East, the endemicity of flies increased because of a high suitability. This agreed with the FAO report about the geospatial demarcation of OWSF in the Middle East 51 . This report confirmed the influence of temperature on the potential distribution of OWSF in the Middle East.…”
Section: Discussionsupporting
confidence: 89%
“…Another powerful and updated predictive tool is Maxent. Maxent models are characterized by their robust predictive powers for the potential distribution of species 51 . Also, its statistical algorithm is accurate even with small occurrence records.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, analysis of habitat suitability modelling revealed that the susceptibility of invasion by B. terrestris is moderate in northern Honshu, while that in southern Honshu is minimal [58]. Similar results were obtained through MaxEnt analysis [59]. Therefore, we should concentrate our attention on controlling the invasive population of this species on Hokkaido, particularly around the two areas with valuable vegetation, Daisetsu and Notsuke-Furen (Figure 1).…”
Section: Candidate Control Methods Against B Terrestrismentioning
confidence: 55%
“…artificially rear this species in Taiwan (Ho et al 2002). Studies have predicted that large areas of overlapping habitat with imported Bombus terrestris will severely threaten many local bumblebee species, including B. bicoloratus (Naeem et al 2018). As a native species with potential for practical applications, the conservation of B. bicoloratus is of paramount importance.…”
Section: Discussionmentioning
confidence: 99%